2021
DOI: 10.3389/fpls.2021.642581
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Chemical Structures and Biosynthesis of Polyphenols in Nut-Bearing Species

Abstract: Nuts, such as peanut, almond, and chestnut, are valuable food crops for humans being important sources of fatty acids, vitamins, minerals, and polyphenols. Polyphenols, such as flavonoids, stilbenoids, and hydroxycinnamates, represent a group of plant-specialized (secondary) metabolites which are characterized as health-beneficial antioxidants within the human diet as well as physiological stress protectants within the plant. In food chemistry research, a multitude of polyphenols contained in culinary nuts hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 163 publications
0
19
0
Order By: Relevance
“…Moreover, partial isomerisation of pseudodepsides could also take place; an example is the case of p -coumaroylshikimic acids (36, 39), among which one was present in both materials (36) but second only in dried sloes (39). Furthermore, three other drying-related processes, such as the oxidative coupling of caffeoylquinic acids [ 28 ], depolymerisation of condensed proanthocyanidins [ 21 ], and recovery of polyphenols from lignified stone tissue [ 29 ] were probably responsible for the presence of caffeoylquinic acid dehydrodimer (29), (epi)catechin derivative (13), and aromadendrin hexoside (37) in dried fruits, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, partial isomerisation of pseudodepsides could also take place; an example is the case of p -coumaroylshikimic acids (36, 39), among which one was present in both materials (36) but second only in dried sloes (39). Furthermore, three other drying-related processes, such as the oxidative coupling of caffeoylquinic acids [ 28 ], depolymerisation of condensed proanthocyanidins [ 21 ], and recovery of polyphenols from lignified stone tissue [ 29 ] were probably responsible for the presence of caffeoylquinic acid dehydrodimer (29), (epi)catechin derivative (13), and aromadendrin hexoside (37) in dried fruits, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…This leads to an increase in the concentration of catechin, epicatechin, and their oligomers, as well as kaempferol and isorhamnetin. In their study, Aneklaphakij et al [ 32 ] confirmed the presence of chalcones in almond kernel skins. In addition, Khan et al [ 33 ] demonstrated that naringenin and hesperetin chalcones spontaneously undergo cyclization back to the parent flavanones under neutral conditions.…”
Section: Resultsmentioning
confidence: 85%
“…The remaining glycosylated polyphenols were conjugated to galactose (#3, #11, and #20), glucose (#2, #4, #14, #15, and #18), arabinose (#7), diglucoside (#10, #33, #36, and #37), rutinoside (#5, #6, #26, and #34), xylose (#9), sambubiose (#16), or glucuronic acid (#35) moiety. Scientific studies evaluating the potential bioavailability of polyphenols have frequently indicated that aglycones are poorly permeable to biological membranes [ 31 , 35 , 36 , 37 ]. Consequently, potential local activity of these phenols after ingestion of foods enriched with these phytochemicals can be presumed [ 31 , 36 ].…”
Section: Resultsmentioning
confidence: 99%